Incorporating Writing into a Personalized Normative Feedback Intervention to Reduce Problem Drinking among College Students - Young, Chelsie M. (Alcohol Clin Exp Res, 2019)
BACKGROUND: Personalized normative feedback (PNF) interventions have been repeatedly found to reduce drinking among undergraduates. However, effects tend to be small, potentially due to inattention to and inadequate processing of the information. Adding a writing component to PNF interventions may allow for greater cognitive processing of the feedback, thereby boosting intervention efficacy. Additionally, expressive writing (EW) has been shown to reduce drinking intentions; however, studies have not examined whether it can reduce drinking behavior. The present experiment evaluated whether including a writing task would improve the efficacy of PNF and whether EW alone can be used to reduce drinking and alcohol-related problems. METHOD: Heavy drinking undergraduates (N=250) were randomized to receive either: 1) PNF about their alcohol use; 2) EW about a negative, heavy drinking occasion; 3) PNF plus writing about the norms feedback; or 4) attention control feedback about their technology use in an online brief intervention. Participants (N=169) then completed a one-month follow-up survey about their past month alcohol use and alcohol-related problems online. RESULTS: PNF plus writing reduced alcohol-related problems compared to all other conditions. No significant reductions were found for EW. Both PNF and PNF plus writing reduced perceived norms and perceived norms mediated intervention effects for both feedback conditions. CONCLUSIONS: The current findings suggest that adding a writing component to traditional norms-based feedback approaches might be an efficacious strategy, particularly for reducing alcohol-related consequences.